Posterior Reversible Encephalopathy Syndrome in Clinical Toxicology: A Systematic Review of Published Case Reports - Largeau, Bérenger; Boels, David; Victorri-Vigneau, Caroline; Cohen, Clara; Salmon Gandonnière, Charlotte; Ehrmann, Stephan (Frontiers in Neurology, 2020)
BACKGROUND Although several case reports have described posterior reversible encephalopathy syndrome (PRES) in a context of poisoning, to our knowledge, a comprehensive assessment has not been performed. The aim of this systematic review was to raise awareness on poisoning specific PRES features and encourage consistent and detailed reporting of substance abuse and drug overdose associated PRES. METHODS Medline/PubMed, Web of Science and PsycINFO were screened through May 31, 2019 to systematically identify case reports and case series describing PRES associated with poisoning (i.e. alcohol, drugs, illicit drugs, natural toxins, chemical substances) in accidental context, intentional overdose, and substance abuse. The methodological quality of eligible case reports/series was assessed. Patients and exposure characteristics, relevant toxicological, radiological, and clinical data were extracted. RESULTS Forty-one case reports and one case series reporting 42 unique cases were included. The median time to PRES onset from the start of exposure was 3 days (IQR 2 – 10). Acute high blood pressure, visual disturbance and seizure were reported in 70%, 55% and 50% of patients, respectively. The initial clinical presentation was alertness disorders in 64% of patients. Nine patients (21%) required mechanical ventilation. One third of patients (33%) had at least one risk factor for PRES such as chronic hypertension (17%) or acute/chronic kidney failure (24%). The main imaging pattern (67%) was the combination of classical parieto-occipital edema with another anatomical region (e.g., frontal, basal ganglia involvement). Vasogenic edema was found in 86% of patients. Intracranial hemorrhage occurred in 14% of patients. Both brain infarction and reversible cerebral vasoconstriction syndrome were diagnosed in 5% of patients. Three patients (12%, 3/25) had non-reversible lesions on follow-up magnetic resonance imaging. The median time required to hospital discharge was 14 days (IQR 7 – 18). Mortality and neurological recurrence rate were null. CONCLUSIONS Comorbidities such as chronic hypertension and kidney failure were less frequent than in patients with other PRES etiologies. Imaging analysis did not highlight a specific pattern for poisoning-induced PRES. Although less described, PRES in the context of poisoning, which shares most of the clinical and radiological characteristics of other etiologies, is not to be ignored.